Two-year incidence of oral disadvantage, a measure of oral health-related quality of life - CHAMIM, Asykuri Ibn dkk. (Blackwell Synergy, 2003)
Dental research has progressed from describing the burden of oral disease using traditional epidemiologic measures of incidence and prevalence, to measuring how oral disease, oral signs, and oral symptoms affect the daily activities and the overall quality of life of the individual.